2014
DOI: 10.1002/ajh.23708
|View full text |Cite
|
Sign up to set email alerts
|

The impact of race, age, and sex in follicular lymphoma: A comprehensive SEER analysis across consecutive treatment eras

Abstract: The impact of race/ethnicity and the additional factors of age, sex, and socioeconomic status (SES) on follicular lymphoma (FL) outcomes have not been comprehensively studied and are not well defined. We examined population-based FL data from >18,000 patients in SEER-13 (1992-2009) investigating race/ethnicity and the impact of relevant factors including sex, age, and SES. Further, we compared data over two consecutive periods: Era-1 (1992-2000, n = 8,355) and Era-2 (2001-2009, n = 10,475). We identified 18,83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 25 publications
3
35
0
1
Order By: Relevance
“…This finding is consistent with data from American [28, 29] and European [30] studies, ours being the largest study of all the ones published in our continent that can be related to the introduction of R. It has been speculated whether the improvements achieved in support care or even high doses of chemotherapy may have influenced this.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with data from American [28, 29] and European [30] studies, ours being the largest study of all the ones published in our continent that can be related to the introduction of R. It has been speculated whether the improvements achieved in support care or even high doses of chemotherapy may have influenced this.…”
Section: Discussionsupporting
confidence: 92%
“…[11][12][13] However, a constant concern with these tumors with long survival times and many treatments is that overall mortality, in comparison with that of a sex-and agematched general population, is always much higher, as occurs with Hodgkin lymphoma. We observed increases in the OS of patients over the years and diagnostic periods, and they were identifiable for all age and sex groups, including groups at advanced stages.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 110 FL patients treated with chemoimmunotherapy, female patients had better PFS (68% vs. 52% at 4 years; P = 0.036); reasons for this advantage were not identified [19]. A retrospective analysis of the SEER database showed that both males and females experienced improved OS in the contemporary era [20]. Nonetheless, when the sexes were compared, the advantage that females enjoyed before 2002 was mitigated in subsequent years; no data on differences according to age were provided.…”
Section: Discussionmentioning
confidence: 99%